The Features and Specificity of Fair-Trade Social Enterprises - Ewa RADOMSKA (Communications of International Proceedings, 2021)
The aim of this article is to identify the features and specificity of Fair Trade (FT) social enterprises selected from a group of numerous entities operating in the FT sector, focusing on the social and economic dimension of their activities. This research was based on the critical analysis of literature, source materials, research results. The results indicate that the FT sector is diverse in terms of the organisations operating in it, but their common element is that they adopt as their mission the fight against poverty and inequality, the improvement of the situation of small producers from the countries of the global South through commercial activities. Among them there are organisations identified as "100% committed to FT". Taking into account the social and economic dimension of the functioning of these entities, they meet the EMES criteria allowing them to be classified as social enterprises. The specificity of social enterprises of the FT is expressed, among others, in the fact that the subject of trade are certified FT products, and trade relations are based on cooperation (partnership) of all participants in the supply chain, including mechanisms and solutions to support producers within the main international Fair-Trade organisations.
Keywords: Fair Trade; Fair Trade Social Enterprise; World Fair Trade Organisation; Fairtrade Labelling Organisations International; Fairtrade International.